Infectious disease outbreaks in competitive sports. A review of the literature - Turbeville, S. D.; Cowan, L. D.; Greenfield, R. A. (The American Journal of Sports Medicine, 2006)
Recent outbreaks of infectious diseases in athletes in competitive sports have stimulated considerable interest. The environments in which these athletes compete, practice, receive therapy for injuries, and travel, both domestically and internationally, provide varied opportunities for the transmission of infectious organisms. The purpose of this medical literature review is to identify the agents most commonly reported in the medical literature as responsible for infectious disease outbreaks in specific sports and their modes of transmission and to guide targeted prevention efforts. A literature review of English-language articles in medical publications that reported outbreaks of infectious diseases in competitive athletes was conducted in PubMed MEDLINE from 1966 through May 2005. Outbreaks that were solely food borne were excluded. Fifty-nine reports of infectious disease outbreaks in competitive sports were identified in the published medical literature. Herpes simplex virus infections appear to be common among wrestlers and rugby players, with no single strain responsible for the outbreaks. Methicillin-resistant Staphylococcus aureus was responsible for several recent outbreaks of soft tissue and skin infections among collegiate and professional athletes. The most common mode of transmission in outbreaks was direct, person-to-person (primarily skin-to-skin) contact. Blood-borne exposure was implicated in 2 confirmed outbreaks of hepatitis. Airborne and vector transmissions were rarely reported. This review provides an overview of infectious disease outbreaks thought to be either serious enough or unusual enough to report. Appropriate surveillance of the frequency of infections will allow sports medicine staff to identify outbreaks quickly and take necessary measures to contain further transmission and prevent future outbreaks.